2016
DOI: 10.1088/1475-7516/2016/10/007
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological constraints on coupled dark energy

Abstract: The coupled dark energy model provides a possible approach to mitigate the coincidence problem of cosmological standard model. Here, the coupling term is assumed asQ = 3Hξxρx, which is related to the interaction rate and energy density of dark energy. We derive the background and perturbation evolution equations for several coupled models. Then, we test these models by currently available cosmic observations which include cosmic microwave background radiation from Planck 2015, baryon acoustic oscillation, type… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 121 publications
2
38
0
Order By: Relevance
“…Further, from observational point of view, recent data favor the late time interaction between DM and DE [18][19][20][21][22][23]. Also the coupling parameter in the interaction can be measured by various observations [21][22][23][24][25][26][27][28][29][30]. Moreover, it is speculated that class of interacting dark fluid models may resolve the current tensions on σ s and the local value of the Hubble constant H 0 [22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, from observational point of view, recent data favor the late time interaction between DM and DE [18][19][20][21][22][23]. Also the coupling parameter in the interaction can be measured by various observations [21][22][23][24][25][26][27][28][29][30]. Moreover, it is speculated that class of interacting dark fluid models may resolve the current tensions on σ s and the local value of the Hubble constant H 0 [22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Also the coupling parameter in the interaction can be measured by various observations [21][22][23][24][25][26][27][28][29][30]. Moreover, it is speculated that class of interacting dark fluid models may resolve the current tensions on σ s and the local value of the Hubble constant H 0 [22][23][24][25][26][27][28][29][30][31]. Additionally, cosmologists are of the opinion that the interaction between the dark sectors may leave an imprint on the perturbation analysis and as a result there may be significant changes in the lowest multipoles of the CMB spectrum [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Essentially these interacting models invoke energy exchange between the dark components and a small degree of momentum exchange. These scenarios have been intensively investigated in the literature for several dark sector coupling functions and observational approximations [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. It has recently been shown that the current observational data can favor the late time interaction between DE and DM [27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The constraint results presented that the mean values of interaction rate was ξ x = −0.61 + 0.12 − 0.25 at 1σ level. The constraint results of energy exchange Q = 3Hξρ x from CMB, BAO, SNIa, Redshift-space distortions (RSD) [69] have shown that the interaction rate was the order of 10 −3 at 1σ level, there was no evidence for the coupling between dark energy and dark matter [41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%